THE FUTURE OF ACCOUNTING’S PAST: A REFLECTION ON ITS CONTEMPORARY RELEVANCE - François COETZEE; Pieter BUYS (Studia Universitatis Babeș-Bolyai. Philosophia, 2015)
Contemporary corporate history demonstrates that, though accounting is acknowledged as the language of business, there are more and more cases where this language becomes an incomprehensible foreign language. The objective of accounting as promulgated by accounting regulators is characterized by large volumes of complex principles, which none but the most specialised accounting professionals can interpret. This very often results in many classes of accounting information users not being able to properly understand the message being conveyed. This paper aims to reflect on the primary objective of accounting by considering its historic evolution from its ancient roots as a record keeping function, through its bookkeeping phases up to when it actually began to resemble accounting as we know it in the contemporary business environment. Throughout this reflection, consideration is given to its intended purpose for the specific time period under consideration. The paper concludes that even though accounting has evolved much in its perceived objectives, the complexity of the contemporary business environment contributed to complex accounting principles and practices. Nonetheless, the key purpose of accounting should never be lost, that being that it is the language of business and as such it must be understandable to business stakeholders.